Aiming Talent Development Toward Creative Eminence in the 21st Century. Issue 3 (2nd July 2016) - Olszewski-Kubilius, Paula; Subotnik, Rena F.; Worrell, Frank C.
Abstract : Much has been written about the social and scientific problems that face the world in the 21st century, including climate change and economic inequality. In this context, the development of talented individuals who can tackle these problems is most important. In this article, the authors discuss the implications of 21st-century challenges for the development of talent based on their megamodel (Subotnik, Olszewski-Kubilius, & Worrell,  2011), with a particular focus on the psychosocial skills that will be important for 21st-century learning and working environments.